Manajemen Penilaian Kinerja Guru Dalam Proses Pembelajaran (Studi Kasus Madrasah Aliyah Persis Lempong Garut) - Ramadhan, Fahri Sahrul; Hafid, Abdul; Badrudin, Badrudin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Teacher professionalism will never be separated from attention to their performance. This research aims to find out in general about teacher performance assessment management (PKG), especially in the learning process. The procedures for collecting data were carried out using observation, interviews and documentation methods with the main sources being Madrasah Heads, Teachers and other stakeholders, so that the research results showed that the management of teacher performance evaluation at MA Persis Lempong was divided into; Teacher Performance Assessment Planning, which includes; (1) PKG Preparation Stage, (2) PKG Team Formation Stage, (3) PKG Schedule Determination Stage. Implementation of Teacher Performance Assessment, which includes; (1) Teacher Performance Appraisal Time, (2) Teacher Performance Appraisal Instrument, (3) Teacher Performance Appraisal Method. And Evaluation of Teacher Performance Assessment at MA Persis Lempong – Garut.